1995
DOI: 10.3354/meps129165
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of trace elements ingested by the mussel Mytilus edulis:effects of algal food abundance

Abstract: Pulse-chase feeding and multi-labeled radiotracer techniques were employed to measure the assimilation of 6 trace elements ( l l O m~g , 2 4 1~m , '09Cd, 5 7~o , '$Se and "~n ) from ingested diatoms in the mussel Mytilus e d u l~s feeding at different rates (0.1, 0.49 and 1.5 mg dry wt h-'). Uniformly radiolabeled diatoms Thalassiosira pseudonana were fed to mussels for 0.5 h, and the behavior of the radiotracers in individual mussels was followed for 96 h in a depuration seawater system. Assimilation effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
148
3
8

Year Published

1998
1998
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(174 citation statements)
references
References 32 publications
15
148
3
8
Order By: Relevance
“…In other studies, inverse relationships have also been reported between IR and the AE of phosphorus by Chaoborus trivittatus (Giguère 1981) and of Cd by marine mussels (Wang et al 1995).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In other studies, inverse relationships have also been reported between IR and the AE of phosphorus by Chaoborus trivittatus (Giguère 1981) and of Cd by marine mussels (Wang et al 1995).…”
Section: Discussionmentioning
confidence: 89%
“…This increase could be explained if a greater food consumption led to either a higher metabolic rate, and thus a higher loss rate of Cd, or to differences in digestive processes, as has been observed in mussels (Wang et al 1995). The biological half-life (t 1/2 ) of Cd decreased from 117 to 22 d with increasing food density ( Table 2).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…'OgCd-AE is defined as the proportion of ingested '09Cd retained after digestion of selected seston and gut evacuation. Wang et al (1995) noted that less than 10% of 2 4 1~m was retained in soft tissue after a 24 h depuration period, and most unassimilated Io9Cd was egested within the first 17 h, after which very little Io9Cd appeared in the FE or was lost from tissues. Based on this, 'OgCd-AE was determined after a 24 h depuration period.…”
Section: Mixture Of Labeledmentioning
confidence: 99%
“…Given the now recognized importance of incorporating AE into predictive models of metal accumulation, over the last 5 yr a number of studies have reported AEs for several metals, most notably cadmium, silver, cobalt and chromium, by invertebrates, from a variety of substrates, including algae (Borchardt 1983, Harvey & Luoma 1985. Zang et al 1990, Absil et al 1994, Wang et al 1995 organically coated silica beads (Decho & Luoma 1994), and natural sediment (Gagnon & Fisher 1997). …”
Section: Introductionmentioning
confidence: 99%